A militância político-torcedora no campo futebolístico brasileiro - Gomes, Vitor (2020)
This dissertation has as its central theme the phenomenon of soccer fan political groups in Brazil. Most of them originated between 2013 and 2014, due to the changes brought to Brazil by the reception of the 2014 World Cup, the groups were formed from the club identification and common political affiliation among its members. The guidelines to their performances deal with a series of different oppression processes identified in Brazilian soccer, such as sexism, homophobia, racism and the elitization of stadiums. These groups use social media, especially Facebook, as the main way of spreading their ideas and actions, sharing characteristics with contemporary social movements network, as described by Manuel Castells. The analysis of this research is based centrally on Pierre Bourdieu's concept of field, which had the investigation about the power and hierarchy relations between different groups of agents located in the brazilian soccer field as a reserach problem. The soccer team fan groups, are new social constructions and considered outsiders, engaging to dispute influence with better-established agents, such as the media and communication groups, state representatives, sports institutions and the torcidas organizadas, which hold similarities with ultras in Europe and the barras in Latin America. The production of data was based on the observation of the digital pages of all the collectives and on interviews with two specific groups, "Palmeiras Antifascista" and "Palmeiras Livre". The results show these groups occupying a position of little influence and hierarchy among the analyzed agents. While trying to influence the discourses produced about soccer and politics in the media, the collectives will face a certain type of regionalism as a reactionary force and obstacle to the possibility of national articulation between them, the groups of fans from different brazilian clubs, as well as the tense relations involving contact with torcidas organizadas of football.